4
$\begingroup$

What is the probability that in a group of $n$ people, every month of the year has at least one birthday.

This is my approach:

We have 12 months, and the probability that a month has at least one birthday =$1-(11/12)^n$.

And to find the probability that every month has at least 1 birthday I am trying to use the inclusion exclusion formula. But I am not able to proceed for the probability that there is at least one birthday for each of 2 months. Is my approach correct?

$\endgroup$
  • $\begingroup$ Are you assuming that months have equal lengh? $\endgroup$ – 5xum Oct 4 '16 at 11:24
  • $\begingroup$ yes, I am assuming that all months have equal days $\endgroup$ – anil jack Oct 4 '16 at 11:25
  • 2
    $\begingroup$ Have you done the question specifically for $n = 11, 12$ and $13$? That might give you insight into how to do it generally. $\endgroup$ – Arthur Oct 4 '16 at 11:26
  • $\begingroup$ For n=13 is this the right answer? (12c1)*(13c2)*(11!)/(12)^13. That is i am selecting one month which will have 2 birthdays and then selecting two people out of 13 for that month and remaining 11 people in 11! ways $\endgroup$ – anil jack Oct 4 '16 at 11:33
  • $\begingroup$ Duplicate of (math.stackexchange.com/q/141655) $\endgroup$ – Jean Marie Oct 4 '16 at 12:50
5
$\begingroup$

The probability that $n$ people miss $k$ months is $N_n(k)=\binom{12}{k}\left(\frac{12-k}{12}\right)^n$. Therefore, by Inclusion-Exclusion, the probability of missing at least one month is $$ \sum_{k=1}^{12}(-1)^{k-1}\binom{12}{k}\left(\frac{12-k}{12}\right)^n\tag{1} $$ Therefore, the probability of getting all months is $$ \bbox[5px,border:2px solid #C0A000]{\sum_{k=0}^{12}(-1)^k\binom{12}{k}\left(\frac{12-k}{12}\right)^n}\tag{2} $$


We can simplify $(2)$ using Stirling Numbers of the Second Kind $$\newcommand{\stirtwo}[2]{\left\{{#1}\atop{#2}\right\}} \begin{align} \sum_{k=0}^{12}(-1)^k\binom{12}{k}\left(\frac{12-k}{12}\right)^n &=\frac1{12^n}\sum_{k=0}^{12}(-1)^k\binom{12}{k}\,k^n\tag{3}\\ &=\frac1{12^n}\sum_{k=0}^{12}(-1)^k\binom{12}{k}\sum_{j=0}^n\binom{k}{j}\stirtwo{n}{j}j!\tag{4}\\ &=\frac1{12^n}\sum_{j=0}^n\sum_{k=0}^{12}(-1)^k\binom{12}{j}\binom{12-j}{k-j}\stirtwo{n}{j}j!\tag{5}\\ &=\frac1{12^n}\sum_{j=0}^n[j=12]\binom{12}{j}\stirtwo{n}{j}j!\tag{6}\\ &=\bbox[5px,border:2px solid #C0A000]{\frac{12!}{12^n}\stirtwo{n}{12}}\tag{7} \end{align} $$ Explanation:
$(3)$: substitute $k\mapsto12-k$
$(4)$: $k^n=\sum\limits_{j=0}^n\binom{k}{j}\stirtwo{n}{j}j!$
$(5)$: $\binom{12}{k}\binom{k}{j}=\binom{12}{j}\binom{12-j}{k-j}$
$(6)$: $\sum\limits_{k=0}^{12}(-1)^k\binom{12-j}{k-j}=[j=12]$ using Iverson Brackets
$(7)$: evaluate the sum (set $j=12$)

$\endgroup$
  • $\begingroup$ checked numerically , it's ok $\endgroup$ – user354674 Oct 4 '16 at 15:06

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.